Jibanananda Das’er Chhotogolpo: ` Tosya’ Maddhabitto Nari (Jagannath University Journal of Arts, 2026)
In Bengali literature, Jibanananda Das (1999-1954) has cemented his legacy as a poet. However, the stories discovered after his death later brought him recognition as a story writer as well. He wrote a total of 108 stories. The stories reflect the existential crisis of middle-class life. Women have no distinct history as part of the middle class. In the 1930s, when Jibanananda Das was engaged in story writing, the concept of women’s professional life, wealth, and status had not yet been established in society. A woman’s class position as a middle-class individual is subordinate to that of a middle-class man or his family. In Jibanananda Das’s stories, women are portrayed as educated and self-aware. However, their professional lives held no significance in society. Although the nineteenth-century Bengal Renaissance emphasized women’s education and social freedom but the question of their economic independence remained neglected. The women in His stories are confined to household responsibilities and child-rearing, reflecting the broader marginalization of women’s labor. This confinement raises a crucial social inquiry: how should the class position of domestic women be understood? This research aims to analyze the socio-structural framework of middle-class women in Jibanananda Das’s stories. An analytical approach will be followed in the present research paper. Through this analysis, it is possible to gain a clear understanding of the rise and development of middle-class women as social and cultural entities. This analysis also examines the intersection of gender, economy, and social structure in colonial Bengal.Jagannth University Journal of Arts, v-15, i-01, 2025: p14-25